الاستعارة والكناية في الأحاديث النبوية الواردة في "الأربعين" للنووي - UINSU, Tonang (Al-Ḍād Journal, 2020)
The metaphor and metonymy is one of the important rhetorical arts, which is witnessed by Arabic language, the holy Qurʼan, and the prophetic Ḥadith. This research is a new attempt to study the metaphor and metonymy in the Prophetic Ḥadith only, as it formed in the Ḥadith a stylistic phenomenon, in which the characteristics of a comprehensive speech are manifested. The choice is based on some of the prophetic Ḥadith that selected from the book: “The forty” authored by al-Imam Nawawi -for the example, but not on the basis of the limitation- because they are famous narrations narrated by the senior and young narrators. The reason for choosing this topic is the nature of the subject itself, which is aimed at an important technical objective. Each of the metaphor and metonymy is the essence of rhetoric in Arabic, where it extracts the understanding of speech to increase the longing, magnification and ratification of the words of the Prophet Muḥammad (peace be upon him) on the one hand. On the other hand, there is a great linguistic wealth in the Ḥadith of the Prophet Muḥammad to study, especially in the field of metaphor and metonymy as the rhetorical study, which did not find the right luck in terms of research and study independently to give them their right and reveal their secrets.